A High-Voltage, Dendrite-Free, and Durable Zn–Graphite Battery - Wang, Gang; Kohn, Benjamin; Scheler, Ulrich; Wang, Faxing; Oswald, Steffen; Loeffler, Markus; Tan, Deming; Zhang, Panpan; Zhang, Jian; Feng, Xinliang (Advanced Materials, 2020)
The intrinsic advantages of metallic Zn, like high theoretical capacity (820 mAh g−1), high abundance, low toxicity, and high safety have driven the recent booming development of rechargeable Zn batteries. However, the lack of high-voltage electrolyte and cathode materials restricts the cell voltage mostly to below 2 V. Moreover, dendrite formation and the poor rechargeability of the Zn anode hinder the long-term operation of Zn batteries. Here a high-voltage and durable Zn–graphite battery, which is enabled by a LiPF6-containing hybrid electrolyte, is reported. The presence of LiPF6 efficiently suppresses the anodic oxidation of Zn electrolyte and leads to a super-wide electrochemical stability window of 4 V (vs Zn/Zn2+). Both dendrite-free Zn plating/stripping and reversible dual-anion intercalation into the graphite cathode are realized in the hybrid electrolyte. The resultant Zn–graphite battery performs stably at a high voltage of 2.8 V with a record midpoint discharge voltage of 2.2 V. After 2000 cycles at a high charge–discharge rate, high capacity retention of 97.5% is achieved with ≈100% Coulombic efficiency.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anion intercalation; dendrite-free; dual-ion batteries; graphite cathodes; Zn batteries